THE IMPLICATIONS OF KNOWLEDGE MANAGEMENT STRATEGY IN REDUCING STRATEGIC MYOPIA - Hana Jasim Mohammed; Firas Adnan Abbas Altabtabae (Scholar Express Journals, 2022)
The purpose of the present study is to identify the role of the knowledge management strategy (System-oriented Strategy, People-oriented Strategy) in reducing strategic myopia (spatial and temporal), and the use of resolution as a key tool for collecting the necessary data to achieve its objective. A number of (60) forms were distributed to determine the level of knowledge management strategy availability and strategic myopia, and (57) were retrieved, and after tabulation the data showed that the valid questionnaires (53) were a questionnaire, in addition to using a combination of statistical methods, represented by the weighted mean, standard deviation, and simple correlation coefficient. The results of the study showed that there is a positive correlation between the knowledge management strategy and strategic myopia, since the application of the knowledge management strategy reduces strategic myopia, thus making it possible to assert that the application and increased awareness of the studied sample leads to the development of the potential of the institutions studied.
Keywords: knowledge; management; strategy; myopia